Neuroprotection of Rotenone-Induced Parkinsonism by Ursolic Acid in PD Mouse Model - Zahra, Walia; Rai, Sachchida N.; Birla, Hareram; Singh, Saumitra Sen; Rathore, Aaina Singh; Dilnashin, Hagera; Singh, Richa; Keswani, Chetan; Singh, Rakesh K.; Singh, Surya Pratap (CNS & Neurological Disorders - Drug Targets, 2020)
Background: Parkinson’s Disease (PD) is characterized by both motor and non-motor symptoms. The presynaptic neuronal protein, α-Synuclein, plays a pivotal role in PD pathogenesis and is associated with both genetic and sporadic origin of the disease. Ursolic Acid (UA) is a well-known bioactive compound found in various medicinal plants, widely studied for its anti-inflammatory and antioxidant activities. Objective: In this research article, the neuroprotective potential of UA has been further explored in the Rotenone-induced mouse model of PD. Methods: To investigate our hypothesis, we have divided mice into 4 different groups, control, drug only control, Rotenone-intoxicated group, and Rotenone-intoxicated mice treated with UA. After the completion of dosing, behavioral parameters were estimated. Then mice from each group were sacrificed and the brains were isolated. Further, the biochemical tests were assayed to check the balance between the oxidative stress and endogenous anti-oxidants; and TH (Tyrosine Hydroxylase), α-Synuclein, Akt (Serine-threonine protein kinase), ERK (Extracellular signal-regulated kinase) and inflammatory parameters like Nuclear Factor-ΚB (NF-ΚB) and Tumor Necrosis Factor- α (TNF-α) were assessed using Immunohistochemistry (IHC). Western blotting was also done to check the expressions of TH and α-Synuclein. Moreover, the expression levels of PD related genes like α-Synuclein, β-Synuclein, Interleukin-1β (IL-1β), and Interleukin-10 (IL-10) were assessed by using Real-time PCR. Results: The results obtained in our study suggested that UA significantly reduced the overexpression of α-Synuclein and regulated the phosphorylation of survival-related kinases (Akt and ERK) apart from alleviating the behavioral abnormalities and protecting the dopaminergic neurons from oxidative stress and neuroinflammation. Conclusion: Thus, our study shows the neuroprotective potential of UA, which can further be explored for possible clinical intervention.
Keywords: Parkinson' s disease